2016
DOI: 10.1152/jn.00130.2016
|View full text |Cite
|
Sign up to set email alerts
|

Sour taste increases swallowing and prolongs hemodynamic responses in the cortical swallowing network

Abstract: Sour stimuli have been shown to upregulate swallowing in patients and in healthy volunteers. However, such changes may be dependent on taste-induced increases in salivary flow. Other mechanisms include genetic taster status (Bartoshuk LM, Duffy VB, Green BG, Hoffman HJ, Ko CW, Lucchina LA, Weiffenbach JM. Physiol Behav 82: 109-114, 2004) and differences between sour and other tastes. We investigated the effects of taste on swallowing frequency and cortical activation in the swallowing network and whether taste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 68 publications
2
20
0
Order By: Relevance
“…The finding that citrus juice eased the swallowing of food ingested after its intake was in agreement with a study by Mulheren (2016), which showed that sour products increased swallowing frequency after intake [16]. This was also seen in our results, where there was an increase in the ease of swallowing the cracker after most of the test products.…”
Section: Discussionsupporting
confidence: 93%
“…The finding that citrus juice eased the swallowing of food ingested after its intake was in agreement with a study by Mulheren (2016), which showed that sour products increased swallowing frequency after intake [16]. This was also seen in our results, where there was an increase in the ease of swallowing the cracker after most of the test products.…”
Section: Discussionsupporting
confidence: 93%
“…A third consideration involves the extant neuroscience literature regarding taste-related sensation, or rather the gaps that exist in our current understanding of the complex underlying networks. Investigators using various stimuli and neuroimaging technologies have identified a range of brain regions and timing patterns that appear to be involved in the processing of taste stimuli generally (Babaei et al, 2010;Humbert and Joel, 2012), and specifically with regard to GTS (Bembich et al, 2010;Eldeghaidy et al, 2011;Mulheren et al, 2016). While all of these contributions are valuable, a clear picture of the neural pathways for processing of the multimodal inputs associated with taste stimulation, much less one that accounts specifically for GTS, has yet to emerge.…”
Section: Discussionmentioning
confidence: 99%
“…Eldeghaidy et al (2011) further investigated other brain regions that may be differentially activated based on GTS, and reported significant positive correlations between blood oxygen level-dependent (BOLD) responses and GTS in primary and secondary somatosensory cortices (SI, SII) the anterior cingulate cortex, and the anterior-, mid-, and posterior-insula after varied concentrations of isoviscous and isosweet fat emulsions. A functional near infrared spectroscopy (fNIRS) study by Mulheren et al (2016) found no significant differences in hemodynamic activity among GTS groups in the sensorimotor cortices using sweet and sour stimuli. Similar to the neuroimaging literature, the evidence of an effect of GTS on swallowing biomechanics is also mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Among taste qualities, use of sour bolus such as carbonated [ 60 ] and citric acid liquids (e.g., lemon juice) [ 61 , 62 ] are the popular approaches for the treatment of dysphagia, and the studies reported therapeutic potential of using such stimuli in dysphagia rehabilitation. Mulheren et al showed that a sour bolus (0.08 M citric acid) induces larger response in the cerebral cortex as well as increase in the frequency of swallowing to a greater degree than water and sweet stimuli in 15 healthy subjects [ 63 ]. Recently, Elshukri et al tested the effects of 5-ml liquid bolus swallows of carbonated, citric acid, and still water on volitional swallowing performance and corticobulbar excitability evaluated by pharyngeal MEPs in healthy adults [ 64 •].…”
Section: Somatic and Chemical Stimulationmentioning
confidence: 99%